Regularity of Commutators of the One-Sided Hardy-Littlewood Maximal Functions. (13th July 2020) - Zhang, Daiqing
Abstract : In this paper, the regularity properties of two classes of commutators of the one-sided Hardy-Littlewood maximal functions and their fractional variants are investigated. Some new bounds for the derivatives of the above commutators and the boundedness and continuity for the above commutators on the Sobolev spaces will be presented. The corresponding results for the discrete analogues are also considered.